De autor a personagem: Jorge Luis Borges na mira de romancistas latino-americanos - Milreu, Isis [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Jorge Luis Borges is regarded as one of the most important XX century writers from many critics’ and writers’ standpoint. Therefore, his poetry, which became a paradigmatic one, has revolutionized the literary practice as well as the literary studies. Currently, we observe that the Argentinian writer is not only analyzed in several essays, theses and biographies, but also the writer himself has been converted into a recurring character in various novels, short stories, chronicles, plays, films and comics. In this sense, Pablo Brescia (2008) points out that there is a tendency in fictionalizing Borges, that is, to make him into a literary object. Brescia adds that instudies on Borges there is still an ignored aspect concerning the way some writers have (re)read the Argentinian author, especially within the fictional sphere. Considering the existence of that gap we may justify the accomplishment of a study about this topic. Thus, this research work aims at contributing to the understanding of the process of Borges’ conversion into a character in the production by other writers, specifically within the scope of Latin American literature, such as, the Argentinian and Brazilian ones. Thereby, the corpus of this research consists of the following novels: Jorge Manzur’s El simulador (1990); María Rosa Lojo’s Las libres del Sur. Una novela sobre Victoria Ocampo (2004); Francisco Cappellotti’s Matar a Borges (2012); Luis FernadoVeríssimo’s Borges e os orangotangos eternos (2000); Hamilton Alves’s O romance de Borges (2000); and Antonio Fernando Borges’s Memorial de Buenos Aires (2006). We observe that those narratives are structured around Borges’ biografemas and his literature which dialogs with both Borges’ poetry and the history of literature, besides utilizing intertextuality and metafiction as main stylistic features

Jorge Luis Borges é considerado por muitos críticos e escritores um dos autores mais importantes do século XX. Afinal, sua poética revolucionou a prática literária, bem como os estudos de literatura, tornando-se paradigmática. Atualmente, observamos que o escritor argentino não é apenas alvo de inúmeros ensaios, teses e biografias, mas também foi convertido em personagem de vários romances, contos, crônicas, peças teatrais, filmes e até histórias em quadrinhos. Nesse sentido, Pablo Brescia (2008) assinala que há uma tendência a literaturizar Borges, isto é, transformá-lo em objeto literário. O estudioso acrescenta que nos estudos borgeanos ainda há um espaço ignorado sobre o modo como os escritores (re) leram o autor argentino, particularmente, no âmbito ficcional. Considerando a existência da referida lacuna, entendemos ser justificável a realização de um estudo que examine esta questão. Assim, o objetivo de nosso trabalho é contribuir para a compreensão do processo de conversão de Borges em personagem de outros autores, especificamente, no âmbito das literaturas argentina e brasileira, ou melhor, latino-americana. Destarte, selecionamos como corpus desta pesquisa os seguintes romances: El simulador (1990), de Jorge Manzur; Las libres del Sur. Una novela sobre Victoria Ocampo (2004), de María Rosa Lojo, Matar a Borges (2012), de Francisco Cappellotti, Borges e os orangotangos eternos (2000), de Luis Fernando Veríssimo; O romance de Borges (2000), de Hamilton Alves e Memorial de Buenos Aires (2006), de Antonio Fernando Borges. Observamos que essas narrativas giram em torno de biografemas de Borges e de sua literatura, dialogam com a poética borgeana e a história da literatura, além de utilizarem a intertextualidade e a metaficção como principais recursos estilísticos
Keywords: Borges, Jorge Luis 1899-1986; Literatura e história; Personagens literários; Literatura latino-americana; Literatura comparada; Latin American literature